Games adapted to stimulate visual memory in schoolchildren with mild intellectual disabilities (Original) (Revista científica Olimpia, 2020)
Schoolchildren with Intellectual Disabilities inserted into general education demand a greater effort from the professionals who guide their teaching-educational process and much more, for those who use adapted physical activity as a fundamental means of raising their quality of life and social insertion. The purpose of this article is to stimulate visual memory in children diagnosed with Mild Intellectual Disability based on the application of games with pedagogical adaptations, since the results of tests and applied tests highlight the need to address this problema.
Keywords: intellectual disability; visual memory; adapted games